2019
DOI: 10.4028/www.scientific.net/kem.797.411
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ZnO Nanoparticles for Wax Deposition Control and Oil Upgrading: Effect of Ratio of Zinc Acetate Dihydrate to Oxalic Acid Dihydrate

Abstract: In the current paper, fundamental aspects of heavy oil and wax deposition problems are defined. Wax or in another term is cloud point occur when the oil starts to precipitate. When it’s started to precipitate, it can cause major problem to industry of oil and gas. In this study, ZnO nanoparticles were chosen to study the effect of varying molar ratio from 1:1, 1:2, 1:3 to the morphology and size of the nanoparticle. The structures and properties were recognized with energy dispersive X-ray (EDX), field emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Nevertheless, a further investigation demonstrated that by blending the surfactants with 1 wt % of a nanofluid (prepared with xylene and 400 mg·L –1 of SiO 2 nanoparticles), the wax deposition decreased up to 63.4, 64.8, 81.4, 73.1, and 55.9% for the crude oil in the presence of S1, S2, S3, S4, and S5 surfactants, respectively, revealing the exceptional ability of the nanoparticles for inhibiting wax deposition . Hussein et al studied the influence of several types of nanoparticles on the rheological behavior and wax content of model oils, including Fe 2 O 3 , ZnO, and MgO nanomaterials. From the study, the addition of 1000 mg·L –1 of ZnO nanoparticles with particle sizes of 10.37 and 16.37 nm to the crude oil reduced wax deposition by 27.18 and 49.83, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a further investigation demonstrated that by blending the surfactants with 1 wt % of a nanofluid (prepared with xylene and 400 mg·L –1 of SiO 2 nanoparticles), the wax deposition decreased up to 63.4, 64.8, 81.4, 73.1, and 55.9% for the crude oil in the presence of S1, S2, S3, S4, and S5 surfactants, respectively, revealing the exceptional ability of the nanoparticles for inhibiting wax deposition . Hussein et al studied the influence of several types of nanoparticles on the rheological behavior and wax content of model oils, including Fe 2 O 3 , ZnO, and MgO nanomaterials. From the study, the addition of 1000 mg·L –1 of ZnO nanoparticles with particle sizes of 10.37 and 16.37 nm to the crude oil reduced wax deposition by 27.18 and 49.83, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a further investigation demonstrated that by blending the surfactants with 1 wt % of a nanofluid (prepared with xylene and 400 mg inhibiting wax deposition. 55 Hussein et al 58 studied the influence of several types of nanoparticles on the rheological behavior and wax content of model oils, including Fe 2 O 3 , ZnO, and MgO nanomaterials. From the study, the addition of 1000 mg•L −1 of ZnO nanoparticles with particle sizes of 10.37 and 16.37 nm to the crude oil reduced wax deposition by 27.18 and 49.83, respectively.…”
Section: Introductionmentioning
confidence: 99%